2014
DOI: 10.1590/s0034-759020140606
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho de fusões e aquisições cross border: análise empírica do caso brasileiro

Abstract: Desempenho de fusões e aquisições cross border: análise empírica do caso brasileiro Desempeño de fusiones y adquisiciones cross border: análisis empírico del caso brasileño ABSTRACTThe purpose of this article is to investigate whether the cross-border acquisitions made by Brazilian companies over the past 15 years have improved their financial performance. Drawing on institutional, sociocultural, and organizational learning theories, this study develops and empirically tests several hypotheses on the determina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 38 publications
0
6
0
11
Order By: Relevance
“…Their results showed significant improvements in the firms' performance after M&A operations (domestic and cross-border), regarding the following variables: sales, net profits, assets, dividends, and, to a lesser extent, the ratio, net profits/sales. Bortoluzzo et al (2014) investigated whether the acquisitions made by Brazilian firms abroad contributed to their financial performance. The authors found that, in fact, investing abroad through cross-border activities improves the performance of Brazilian firms when the cultural distance between home and host countries is low or medium, and the institutional environment in which they operate is developed.…”
mentioning
confidence: 99%
“…Their results showed significant improvements in the firms' performance after M&A operations (domestic and cross-border), regarding the following variables: sales, net profits, assets, dividends, and, to a lesser extent, the ratio, net profits/sales. Bortoluzzo et al (2014) investigated whether the acquisitions made by Brazilian firms abroad contributed to their financial performance. The authors found that, in fact, investing abroad through cross-border activities improves the performance of Brazilian firms when the cultural distance between home and host countries is low or medium, and the institutional environment in which they operate is developed.…”
mentioning
confidence: 99%
“…The larger the experience of the MNC with the host country and with acquisitions, the lower will probably be the perceived complexities and thus the lower the temporal hiatus between acquisition announcement and finalization (Dikova et al, 2010). In sum, in the negotiation stage of the acquisition process, it seems reasonable to suggest that prior acquisition experience, and especially acquisition experience in the same country, may facilitate the finalization of the acquisition (Bortoluzzo et al, 2014).…”
Section: Acquisition Experiencementioning
confidence: 99%
“…As teorias que surgiram das instituições, e que analisam o impacto da distância cultural, as diferenças regulatórias e as contingências institucionais nos eventos de reestruturação corporativa, são cada vez mais numerosas hoje em dia (BORTOLUZZO et al, 2014), isso se deu porque análises mais tradicionais centradas apenas nos aspectos econômicos e de mercado se revelaram insuficientes para apreender toda a complexidade inerente a um processo de incorporação.…”
Section: Alternativas Para a Análise Do Casounclassified